Analisis Strategi Peningkatan Pelayanan Housekeeping Berdasarkan Guest Comment di Online Platform Best Western The Lagoon Hotel Manado - Kuhu, Mikha Tesalonika; Dianne O. Rondonuwu (Jurnal Ilmu Sosial dan Humaniora, 2025)
The hospitality industry is one of the important sectors in supporting the progress of tourism, especially in locations that have tourist attractions such as Manado City with increasing competition, hotels not only provide adequate facilities, but also must be able to provide quality services and leave a positive impression on      guests. One important aspect of hotel service that greatly impacts the visitor experience is cleaning services, which include the cleanliness and tidiness of rooms and other areas in the hotel.  This study aims to analyze the service improvement strategy of Best Western The Lagoon Hotel Manado in handling guest complaints, and identify guest complaints about housekeeping. The research method used is to focus on Guest Comments through Online Trave Agents (OTA). Then the data was collected through documentation methods in the form of comment sources, important documents, and by looking at the internet and OTA, which are related to guest complaints at Best Western The Lagoon Hotel Manado, especially those related to housekeeping.  The results of the study show that there are still many negative responses to improvement strategies. The research results show that many negative responses remain. Improvement strategies should focus on improving cleaning procedures, regular trainingfor the housekeeping team, intensive supervision, and the use of technology to directly monitor performance and guest feedback. The company needs to improve the quality of cleanliness, provide regular training for housekeeping staff, and conduct internal evaluations.